Stillbirth: the impact of antiphospholipid syndrome?. (March 2017) - Herrera, C A; Heuser, C C; Branch, D Ware
Fetal death resulting in stillbirth is generally acknowledged as a feature of antiphospholipid syndrome. Recently published studies appear to confirm the association between antiphospholipid antibodies (aPL) and stillbirth, though additional studies of better design would be welcome. Emerging evidence suggests that treatment with heparin agents and low dose aspirin to prevent fetal death is imperfect. New therapeutic approaches for patients with lupus anticoagulant or triple aPL positivity are needed.